Identification of Klebsilla Spp. From Different Ruminant Secretion in Thi-Qar Province - Agmi , Arjewan Mohsen; Shanan, Hayder Kh.; Sekhi , Rabab Jabbar (American Journal of Biology and Natural Sciences, 2025)
The current styudy explained that detection of Klebsiella species from different infected cattle secretions. 120 samples and swabs were collected divided in to (40 as nasal secretion, 40 as vaginal discharge and finally 40 as a milk samples). These sample cultured on different culture media and identified by using cultural characteristic and microscopic appearance. klebsiella pneumonia Identified using ViteKⅡ system and Confirm the final diagnosed of those organism by using polymerase chain reaction(PCR)assay (16S rRNA). Polymerase chain reaction used to detected some gene K1,K2(which is part of several genes responsible for capsule formation), and also blaSHv gene which is one of the genes related with multy drug résistance. Results show that Klebsiella pneumoniae were isolated in rate (10%) from nasal discharge, while isolated in rate (10%) from milk samples, on the other hand, vaginal secretion not appeared positive result for Klebsiella pneumonia. the result involved that K1,K2 genes were not detected in all samples of K. pneumonia. Also, completely isolates of K. pneumonia harbored blaSHv gene (100%), Also the result included that Klebsiella pneumoniae can be consider as major pathogen responsible for different medical case affected bovine in Al-Shatrah distric in Thi-Qar province.